IMPACT OF COMBINED EXCISE TAX RATES FOR ALCOHOL AND TOBACCO PRODUCTS IN UZBEKISTAN ON INDUSTRY INDICATORS (Marketing Journal, 2025)
The article presents a comprehensive econometric analysis and forecast of production and import turnover in relation to changes in excise tax rates in Uzbekistanʼs alcohol and tobacco sector. The main objective is to assess the expected changes in retail a nd wholesale trade turnover for excisable products - beer, wine, cognac, and tobacco - during 2025 -2027. The results indicate a consistent growth in trade turnover across all types of these goods.
Keywords: Excise tax; alcohol market; tobacco market; retail trade turnover; wholesale trade turnover; economic growth; fiscal policy; macroeconomic analysis; econometric modeling